2015
DOI: 10.1590/1983-1447.2015.02.46299
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care in paediatric oncology: perceptions, expertise and practices from the perspective of the multidisciplinary team

Abstract: The subjects revealed that the team also suffers with the death of a child and, like the family, moves toward the construction of coping mechanisms for the elaboration of mourning. Paradoxically, the team shares knowledge to determine the foundations of a singular therapeutic project and inserts the family in this process so that it can be the protagonist of the child's care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 5 publications
0
20
0
15
Order By: Relevance
“…A study points to the ambivalence between feeling and acting, experienced by health professionals in child care without healing possibilities because the bond that makes them close is the same that makes these professionals suffer when death is near (9) . On the fact that the nurses interviewed have greater difficulty accepting the death of a newborn compared to an adult, the literature shows that any loss is a challenge for people.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study points to the ambivalence between feeling and acting, experienced by health professionals in child care without healing possibilities because the bond that makes them close is the same that makes these professionals suffer when death is near (9) . On the fact that the nurses interviewed have greater difficulty accepting the death of a newborn compared to an adult, the literature shows that any loss is a challenge for people.…”
Section: Discussionmentioning
confidence: 99%
“…Physical and emotional benefits are obtained with these initiatives, both for the newborn, reducing the physical symptoms that cause discomfort, and for his/her family, softening the emotional and spiritual suffering (9) . Other research reinforces the importance of having in the NICU, a placeholder for the neonatal palliative care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…POSW indicated the key role of physicians in formulating treatment protocol, ignoring clients' psychosocial needs in care programs and POSW barely participated in formulation and implementation of care plans. Borland (1981); Kadushin & Kulys (1995) Silva & et al,(2015) indicated weakness among social workers to control the physician-dominated team structure.…”
Section: Discussionmentioning
confidence: 99%
“…For this form of care to occur with respect, professionalism, and the appropriate techniques, the subject of palliative care must be added to the graduate healthcare curricula, including the nursing course. Moreover, chronic diseases, especially cancer, have significant demands in the entire country (5)(6) . In 2001, the National Council of Education approved the national curriculum guidelines of the graduate programme in nursing that defines the principles, foundations, conditions, and procedures of nurses' training (7) .…”
Section: Introductionmentioning
confidence: 99%